2008
DOI: 10.1111/j.1469-8137.2008.02591.x
|View full text |Cite
|
Sign up to set email alerts
|

An illustrated gardener's guide to transgenic Arabidopsis field experiments

Abstract: Summary• Field studies with transgenic Arabidopsis lines have been performed over 8 yr, to better understand the influence that certain genes have on plant performance. Many (if not most) plant phenotypes cannot be observed under the near constant, low-stress conditions in growth chambers, making field experiments necessary. However, there are challenges in performing such experiments: permission must be obtained and regulations obeyed, the profound influence of uncontrollable biotic and abiotic factors has to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 16 publications
1
31
0
Order By: Relevance
“…Even stn7 plants that lack the LHCII kinase and therefore do not perform state transitions at all under similar conditions show only a limited fitness reduction (Frenkel et al, 2008). Clearly, the experimental garden experiment does not pose a sufficient challenge to Arabidopsis plants with respect to state transitions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even stn7 plants that lack the LHCII kinase and therefore do not perform state transitions at all under similar conditions show only a limited fitness reduction (Frenkel et al, 2008). Clearly, the experimental garden experiment does not pose a sufficient challenge to Arabidopsis plants with respect to state transitions.…”
Section: Discussionmentioning
confidence: 99%
“…The reproductive fitness of the plants was determined by estimating seed production as described by Kulheim et al (2002) and Frenkel et al (2008) The plants were grown in an experimental garden in randomized block design as described previously (Frenkel et al, 2008). At maturity, seed production was estimated by counting the number of siliques on all plants and estimating the number of seeds per siliques by counting five siliques per plant.…”
Section: Fitness Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Confocal microscopy images from the mesophyll tissues of 9-d-old seedlings revealed smaller cells in pgr5 grown under fluctuating light compared with the wild type, likely explaining the retarded growth (see Supplemental Figure 1 online). No difference in the size of the pgr5 and wild-type cells Field experiment Natural outdoor conditions in Northern Sweden, with light intensity fluctuating irregularly due to clouds and shading by nearby vegetation (Külheim et al, 2002;Frenkel et al, 2008) 6-week-old mature leaves (4 weeks outside) 1 was observed in seedlings grown under constant light. After 18 d growth under fluctuating light, the pgr5 mutant still remained at the two-or four-leaf state, whereas the wild-type seedlings continued growing ( Figure 1B).…”
Section: Pgr5 Is Essential For Growth Both Under Fluctuating Light Anmentioning
confidence: 98%